When a Thousand Words Are (Not) Enough: An Empirical Study of the Relationship between Firm Performance and Attention to Shareholders - Luciana Carvalho de Mesquita Ferreira (BAR: Brazilian Administration Review, 2015)
The aim of this study is to concurrently test the explanatory power of the attention-based view (ABV) of the firm and of the resource dependence theory (RDT). We propose a conceptual model of attention to shareholders based on assumptions of both ABV and RDT. We test these hypotheses using a unique dataset, consisting of contentanalyzed data on attention allocation for 313 firms from 24 different countries. Our research findings highlight the complementary nature of the RDT and ABV and add to the literature about attention, providing empirical evidence and theoretical explanation for the scarcely explored relationship between firm performance and organizational attention.